Benefit–Risk Assessment of Esketamine Nasal Spray vs. Placebo in Treatment‐Resistant Depression. Issue 2 (13th October 2020) - Katz, Eva G.; Hough, David; Doherty, Teodora; Lane, Rosanne; Singh, Jaskaran; Levitan, Bennett
Abstract : This post hoc analysis assessed the benefit–risk profile of esketamine nasal spray + oral antidepressant (AD) induction and maintenance treatment in patients with treatment‐resistant depression (TRD). The Benefit–Risk Action Team framework was utilized to assess the benefit–risk profile using data from three induction studies and one maintenance study. Benefits were proportion of remitters or responders in induction studies and proportion of stable remitters or stable responders who remained relapse‐free in the maintenance study. Risks were death, suicidal ideation, most common adverse events (AEs), and potential long‐term risks. Per 100 patients on esketamine + AD vs. AD + placebo in induction therapy, 5–21 additional patients would remit and 14–17 additional patients would respond. In maintenance therapy, 19–32 fewer relapses would occur with esketamine. In both cases, there was little difference in serious or severe common AEs (primarily dissociation, vertigo, and dizziness). These findings support a positive benefit–risk balance for esketamine + AD as induction and maintenance treatment in patients with TRD.